2015
DOI: 10.1093/abbs/gmv041
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco carcinogen NNK-induced lung cancer animal models and associated carcinogenic mechanisms

Abstract: Tobacco usage is a major risk factor in the development, progression, and outcomes for lung cancer. Of the carcinogens associated with lung cancer, tobacco-specific nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is among the most potent ones. The oncogenic mechanisms of NNK are not entirely understood, hindering the development of effective strategies for preventing and treating smoking-associated lung cancers. Here, we introduce the NNK-induced lung cancer animal models in different species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 143 publications
(122 reference statements)
2
25
0
Order By: Relevance
“…The control group, which received saline injection, showed no sign of lung tumours ( n = 10). This finding suggested that RBM5 dosage does not affect the initiation of NNK-induced lung cancer and is consistent with previously published data showing that NNK in isolation can induce lung cancer 28 . While not examined at molecular detail here, the histopathological progression of NNK-induced lung cancer progression was consistent with previous publications 28 .…”
Section: Resultssupporting
confidence: 93%
“…The control group, which received saline injection, showed no sign of lung tumours ( n = 10). This finding suggested that RBM5 dosage does not affect the initiation of NNK-induced lung cancer and is consistent with previously published data showing that NNK in isolation can induce lung cancer 28 . While not examined at molecular detail here, the histopathological progression of NNK-induced lung cancer progression was consistent with previous publications 28 .…”
Section: Resultssupporting
confidence: 93%
“…Tobacco smoke is an established risk factor of lung and head and neck cancers [61,62], and is considered to contribute to their recurrence and progression [63,64]. There is evidence that patients with head and neck squamous cell carcinoma often develop primary squamous cell lung carcinoma [65].…”
Section: Discussionmentioning
confidence: 99%
“…NNK is one of the tobacco products that has been evaluated by the International Agency for Research on Cancer (IARC) [73]. Evidence of NNK carcinogenicity was provided by preclinical studies [62]. NNK can be metabolically activated to intermediates that react with DNA forming covalently-bound products known as adducts.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that NNK serves as a tumor initiator and Nic works as a tumor promotion factor to induce breast carcinogenesis in vitro. Several studies have described the proposed role of NNK in tumor initiation . We provide considerable evidence that even very low combined doses of carcinogens, 1pM of Nic and 100 femtM of NNK have a more potent effect on the non‐tumorigenic breast cells during long‐time exposure than their individual doses.…”
Section: Discussionmentioning
confidence: 99%